Assessment of heterogeneous treatment effect estimation accuracy via matching. (29th April 2021) - Gao, Zijun; Hastie, Trevor; Tibshirani, Robert
Abstract : We study the assessment of the accuracy of heterogeneous treatment effect (HTE) estimation, where the HTE is not directly observable so standard computation of prediction errors is not applicable. To tackle the difficulty, we propose an assessment approach by constructing pseudo‐observations of the HTE based on matching. Our contributions are three‐fold: first, we introduce a novel matching distance derived from proximity scores in random forests; second, we formulate the matching problem as an average minimum‐cost flow problem and provide an efficient algorithm; third, we propose a match‐then‐split principle for the assessment with cross‐validation. We demonstrate the efficacy of the assessment approach using simulations and a real dataset.